Factors influencing healthy product consumer behavior: an integrated model of purchase intention - Jessica Müller-Pérez; Ángel Acevedo-Duque; Elizabeth Emperatriz García-Salirrosas; Manuel Escobar-Farfán; Jorge Alberto Esponda-Pérez; Elena Cachicatari-Vargas; Rina Álvarez-Becerra; Sandra Alcina De Fortoul (Frontiers in Public Health)
IntroductionUnderstanding consumer behavior toward healthy food consumption is essential for promoting sustainable and health-conscious dietary choices. Previous studies based on the Theory of Planned behavior (TPB) have highlighted the role of attitude, subjective norms, and perceived behavioral control in shaping purchase intentions. However, the extent to which additional factors, such as price sensitivity, willingness to pay, and health consciousness, influence these decisions remains unclear, particularly in emerging markets. Therefore, this study aims to develop a predictive model to assess the intention to consume healthier products. It is based on the variables of attitude and perceived purchasing control from the Theory of Planned behavior while also incorporating key factors related to sustainability, health, and nutrition. This research addresses the growing need to understand consumer behavior in the context of healthy and sustainable food choices.MethodsA cross-sectional online survey was conducted, collecting data from 703 Mexican consumers. The dataset was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships among the studied variables and their effects on purchase intention and consumer behavior.ResultsThe analysis revealed that willingness to pay was the strongest predictor of healthy purchase intention (β = 0.347, p < 0.001), followed by price considerations (β = 0.325, p < 0.001). Perceived purchase control had a moderate positive effect (β = 0.117, p < 0.009), while attitude also contributed positively, albeit with a smaller effect (β = 0.131, p < 0.001). Health Consciousness, in contrast, exerted only a marginal influence (β = 0.085, p = 0.025), with an insignificant effect size (f2 = 0.007), suggesting a limited role in shaping purchase intentions and highlighting the potential need for greater consumer awareness regarding the benefits of a healthy diet.ConclusionThe findings highlight the pivotal role of price and willingness to pay as key determinants of healthy food purchase intention, underscoring their strategic relevance in influencing consumer behavior. Although perceived purchase control and attitude also contribute positively—albeit to a lesser extent—health consciousness demonstrates limited influence, suggesting that awareness alone may not be sufficient to drive healthier purchasing decisions. These insights offer practical implications for policymakers, health advocates, and marketers seeking to foster healthier consumption habits.